Optimizing Hospital Pharmaceutical Warehouse Operations Using Discrete Event Simulation - Aldi Musliadin; Dwi Apriadi (Jurnal Riset Ilmu Teknik, 2024)
This study aims to analyze and optimize the operational performance of the pharmaceutical logistics warehouse at Hospital Yogyakarta using a Discrete Event Simulation (DES) approach. Preliminary observations revealed a significant workload accumulation during peak hours (09:00–10:55), leading to drug distribution delays, a 10–15% weekly discrepancy between physical and system stock data, and a 12% decline in patient satisfaction. Data were collected through direct work time measurements and secondary hospital records, then modeled using an Activity Cycle Diagram (ACD) and simulated with Arena software. Three improvement scenarios were tested: (1) reassigning goods and invoice verification tasks to the ordering operator, (2) adding one new operator dedicated to the posting activity in the system, and (3) combining both strategies. Simulation results indicate that Alternative III provides the best performance, reducing the average cycle time from 411.4 minutes to 65.57 minutes per cycle, improving productivity by up to 99%, and achieving balanced workloads among operators. These findings demonstrate that DES-based modeling is an effective tool for identifying bottlenecks and designing process improvements without requiring costly technological investment. This research contributes to the field of hospital pharmaceutical logistics management by offering an evidence-based decision-making framework to enhance operational efficiency and service quality sustainably.